Population structure three species of Family Syngnathidae in Merowi River, Kecamatan Kembayan, Kabupaten Sanggau Kalimantan Barat - Kasianus Krisye Firstantha; Tri Rima Setyawati; Riyandi Riyandi; Gema Wahyudewantoro (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Pipe fish is a type of freshwater fish that has potential as ornamental fish. The research objective was to determine the status and habitat conditions of the Merowi River pipe fish as a member of Syngnathidae. The research was conducted from July to December 2019. The research stations were determined based on differences in existing environmental bases. Sampling had done randomly by using scoop net and umbrella fish trap. The data used include population density, age group,test Chi-Square and Principal Component Analysis (PCA). The results showed that 2 genera consisted of 3 species of pipe fish, as much 248 individu. Doryichthys deokhatoides 26 individu (0.042 Catch/Unit Efort); D. martensii 209 individu (0.34 Catch/Unit Efort); Microphis retzii 13 individu (0.02 Catch/Unit Efort). The length of the pipe fish ranged from 48.1 mm to 87.4 mm, and the ratio of male to female is 1: 1 (balanced). The presence of members of Syngnathidae in the Merowi River was effect by temperature and current velocity. Abstrak Ikan pipa adalah salah satu jenis ikan air tawar yang potensial sebagai ikan hias. Penelitian ini bertujuan untuk menganalisis struktur populasi dan kondisi habitat ikan pipa dari famili Syngnathidae di Sungai Merowi. Penelitian dilaksanakan Bulan Juli hingga Desember 2019 pada 10 stasiun pengamatan yang ditentukan berdasarkan tutupan vegetasi dan arus sungai. Pengambilan sampel ikan pipa dilakukan secaracak dengan menggunakan serokan dan perangkap bubu payung. Data yang diperoleh dianalisis kepadatan populasi, kelompok umur, uji Chi-Square dan Analisis Komponen Utama. Hasil identifikasi diperoleh 2 marga dan 3 spesies ikan pipa sebanyak 248 individu yaitu Doryichthys deokhatoides 26 individu (0,042 individu/usaha); D. martensii 209 individu (0,34 individu/usaha); dan Microphis retzii 13 individu (0,02 individu/usaha). Ukuran panjang ikan pipa yang ditemukan berkisar 48,1 mm hingga 87,4 mm. Dari analisis Chi-Square diketahui ikan pipa yang ditemukan memiliki nisbah jantan dan betina 1:1 (seimbang). Kehadiran anggota famili Syngnathidae di Sungai Merowi dipengaruhi oleh faktor suhu dan kecepatan arus.